Spectral analysis of ground magnetic data in Magadi area, Southern Kenya rift - Githiri, JG; Patel, JP; Barongo, JO; Karanja, PK (Tanzania Journal of Science, 2021)
The area surrounding Lake Magadi in the southern Kenya rift is characterized by hot springs that issue from fractures distributed along the shores of the lake. Presence of earthquake swarms that cluster in northern margin of Lake Magadi strongly indicate magmatic activity in the area. This study was done as a follow-up to investigate depth to the heat source possibly causing high seismic activity and high heat flow in the area. A ground magnetic survey was conducted to investigate geothermal potential of the area and a magnetic anomaly contour map prepared. Spectral analysis involving determining power spectrum was applied to magnetic data along selected profiles cutting through discerned anomalies. Spectral analysis results suggest that the Curie-point isotherm depth under Magadi ranges from 5.20 km to 8.30 km. Estimated vertical temperature gradients along the profiles ranges from 111.53°C/km to 69.92°C/km. The hightemperature gradients and relatively shallow Curie point depths indicates high heat flow which suggests presence of a hot magmatic intrusion